Development of Nanofiber Made of Nanocellulose with Oil Encapsulation of Eucalyptus sp. - Sari, Wida Fatma; Haryati, Sri; Mohadi, Risfidian (Science and Technology Indonesia, 2025)
The amalgamation of natural polymers derived from lignocellulosic waste with synthetic polymers is a potential avenue for producing high-value products through nanotechnological innovations. Nanofibers are a significant application of nanotechnology and is now being explored as an alternative method for treating lignocellulosic waste. Nanofiber is a fiber generated by an electrospinning device. Cellulose obtained from lignocellulose can be transformed into valuable products, including nanocellulose. This project entails the synthesis of nanofibers via the combination of natural and synthetic polymers, an innovative approach in the field. Natural polymers are derived from alginate and nanocellulose, whilst synthetic polymers are produced from Poly Vinyl Alcohol (PVA). This study employs nanofibrils in healthcare, specifically as a cartridge filter in masks infused with Eucalyptus sp. This study sought to identify the optimal method for producing nanofibers with a minimal pore size by varying the concentrations of PVA (4%, 8%, 12%, and 16%) and nanocellulose (2.5%, 5%, and 7.5%). This research employs a combination of methods to produce nanocellulose of suitable size, an innovative process. The pretreatment process utilizes a blend of chemical and physical methods. Nanocellulose is synthesized using varying concentrations of sulfuric acid (25%, 50%, and 75%) during the acid hydrolysis process. The optimal nanocellulose size was attained at a sulfuric acid concentration of 50% (40oC, 10 minutes), as evidenced by a mean diameter of 484.3 nm. The amalgamation of physical and chemical methods has demonstrated efficacy in generating a beneficial pore size distribution in nanocellulose. Nanofibers are synthesized utilizing 12% PVA, 0.5% alginate, 2.5% nanocellulose, and 1% Eucalyptus sp. over 30 hours (3 mL), resulting in an average diameter of 200 nm for the created nanofibers. Concurrently, the nanofiber produced in the absence of Eucalyptus sp. exhibited a diameter of 240 nanometers.